1999
DOI: 10.1103/physreve.59.6753
|View full text |Cite
|
Sign up to set email alerts
|

Correlation functions in isotropic and anisotropic turbulence: The role of the symmetry group

Abstract: The theory of fully developed turbulence is usually considered in an idealized homogeneous and isotropic state. Real turbulent flows exhibit the effects of anisotropic forcing. The analysis of correlation functions and structure functions in isotropic and anisotropic situations is facilitated and made rational when performed in terms of the irreducible representations of the relevant symmetry group which is the group of all rotations SO(3). In this paper we firstly consider the needed general theory and explai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
213
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(219 citation statements)
references
References 12 publications
6
213
0
Order By: Relevance
“…It was shown that the leading terms of the inertial-range behavior are the same for isotropic and anisotropic forcing [57,58]. In the papers [59][60][61][62], the velocity correlation functions were decomposed in the irreducible representations of the rotation group. It was argued that in each sector of the decomposition, scaling behavior can be found with apparently universal exponents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the leading terms of the inertial-range behavior are the same for isotropic and anisotropic forcing [57,58]. In the papers [59][60][61][62], the velocity correlation functions were decomposed in the irreducible representations of the rotation group. It was argued that in each sector of the decomposition, scaling behavior can be found with apparently universal exponents.…”
Section: Discussionmentioning
confidence: 99%
“…The picture outlined above for passively advected fields (a superposition of power laws with universal exponents and nonuniversal amplitudes) seems rather general, being compatible with that established recently in the field of NS turbulence, on the basis of numerical simulations of channel flows and experiments in the atmospheric surface layer; see Refs. [57][58][59][60][61][62] and references therein. It was shown that the leading terms of the inertial-range behavior are the same for isotropic and anisotropic forcing [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Here Φ ℓm (r) = r ℓ Y ℓm (r), and see [1] for further details. The first two spherical vectors have a different parity than the third vector, hence the equations for their coefficients are decoupled from the equation for the third coefficient.…”
Section: B the So(3) Decompositionmentioning
confidence: 99%
“…A simple calculation [1] shows that these belong to a twodimensional subspace, which is spanned by the "incompressible vectors"…”
Section: B the So(3) Decompositionmentioning
confidence: 99%
See 1 more Smart Citation